Recenzja monografii Profesora Cezarego Mika, Państwo i prawo wobec procesów internacjonalizacji, integracji i globalizacji, t. I, Wpływ internacjonalizacji i integracji na klasyczny paradygmat państwa prawa oraz t. II, Wpływ globalizacji na klasyczny paradygmat państwa i prawa. W cieniu pandemii Sars-Covid 19 (Toruń: Towarzystwo Naukowe Organizacji i Kierownictwa-Stowarzyszenie Wyższej Użyteczności „Dom Organizatora”, 2022), ss. 614 (t. I), ss. 723 (t. II). - Wiśniewski, Adam (PRAWO i WIĘŹ, 2023)
In his impressive work, Cezary Mik examined the impact of such important processes as internationalization, integration, and globalization on the state and law. This book consists of two volumes and is the first such extensive and comprehensive study of these issues. The first volume is devoted to the impact of internationalization and integration processes, and the second one to globalization. Undoubtedly, the monograph by Cezary Mik deserves high praise for its contribution to an in-depth and comprehensive explanation and determination of the conceptual meaning of such important processes as internationalization, integration, and globalization. It is also a bold attempt to comprehensively analyze the impact of these processes on the functioning of the modern state, national law, the international community, and international law, as well as the relationship between national and international law. Moreover, the contribution of the reviewed work to developing legal sciences needs to be emphasized. The effect of the undertaken analysis is to give legal significance to the studied processes and to demonstrate the relevance and genuine character of their multidimensional impact on the state, law, and the international community. The great value of Mik’s work is undoubtedly the fact that it encourages the perception of the state and law in the broad context of ongoing changes and tendencies while at the same time inspiring to ask numerous questions about their future changes and shape.